Culturas em contato na tradução de Geni Hirata do romance Dragonfly in amber, de Diana Gabaldon - Will, Ana Flavia (2023)
The present research is based on the analysis of Dragonfly in amber (2016), by the North American author Diana Gabaldon, initially written in English, along with its translation to Brazilian Portuguese, A Libélula no Âmbar (2018), by the translator Geni Hirata. Dragonfly in amber (2016) is the second book of the Outlander saga, a series of books which still awaits a conclusion and has received particular attention worldwide in the last decade. Gabaldon’s historic-fictional plot in the first book transits between the post-World War II period, in England, and the years that preceded the Jacobite rising of 1745, in Scotland, from the perspective of an accidental time traveler. In Dragonfly, the plot, which is already more developed, also occurs in 17th-century France. The analysis in this study takes into account the linguistic and cultural aspects which are peculiar to the source novel in the English language, due to the ambiance and narrative historical context that alternates between centuries and countries, accompanied by a cultural and linguistic amalgam in the novel pages. The general objective of this research is to verify the transposition of cultural-linguistic elements in the novel Dragonfly in amber (2016), by Diana Gabaldon, especially when it comes to semantic and lexical issues and linguistic particularities from the source text in English to its translated version in Brazilian Portuguese Geni Hirata, A libélula no âmbar (2018). More specifically, it also aims to point out the impact of choices in the translation process, considering erasings and transpositions, and making suggestions of translations that might eventually be possible. Regarding the methodology, this study is based on bibliographic, documental, and majorly comparative research (GIL, 2008). It is also a descriptive, analytical, and qualitative study (SILVEIRA; CÓRDOVA, 2009) based on the theoretical approach of the Descriptive Studies of Translation. For that, the works of Susan Bassnett (2005) and Itamar Even-Zohar (2012, 2013) will be used to observe aspects of the translation process and cultural aspects of translation. Lawrence Venuti’s theories (2002, 2004) are utilized regarding the configuration of domestication and foreignization, according to the approximation or distancing of the source and the culture of arrival. Besides them, the contributions of André Lefevere (2007) and Paulo Henriques Britto (2017) will be used. Regarding the linguistic-semantic analysis of both texts, Rafael Lanzetti et al.’s (2006) technical procedures of translation are employed. The theories of Antoine Berman (2007) and Mona Baker (1992) are used to discuss thematic networks and chains in the narrative. Some excerpts were selected for the analysis, through which it was verified that there is a tendency to use domestication techniques in the source text, suppressing cultural and linguistic elements, especially dialect marks, which impacts the construction of the semantic chain and interferes with the lexical cohesion of the text in the target language.